DEVELOPMENT OF COPROCESSED EXCIPIENTS OF XANTHAN GUM AND ACACIA GUM AS A CONTROLLED RELEASE MATRIX FOR FAMOTIDINE FLOATING TABLETS - BUDAYA, UNSYURA DHIPA; SURINI, SILVIA (International Journal of Applied Pharmaceutics, 2020)
Objective: Controlled release floating tablets require excipients, which act as a matrix to control the release of the active drug and facilitate the tablet floating in the gastric milieu. One potential excipient is coprocessed excipients of xanthan gum and acacia gum (Co-XG-GA), which is a physical modification of the two natural polymers. In this study, we produced several Co-XG-GA and used them as matrices in floating tablet formulations. Methods: Several coprocessed excipients were prepared from xanthan gum and acacia gum at ratios of 1:1, 1:2, 2:1, 1:3, and 3:1. The obtained excipients were then characterized physically, chemically, and functionally. The coprocessed excipients were then formulated in floating tablets using famotidine as the drug model. The floating tablets were then evaluated in terms of the tablet floating capabilities and the drug release in HCl medium at pH 1.2 for 8 h. Results: Our results showed that the coprocessed excipients were a fine powder, odorless, and a grayish-white color. The excipients had a good swelling index, fairly large viscosity, and good gel strength; hence, they were suitable to be applied as the matrices of floating tablet formulations. The floating tablets of F2, which contained the Co-XG-GA 1:2, demonstrated the best characteristics with 8.33±0.58 min of floating lag time and 24 h of total floating time. Further release studies revealed that the famotidine floating tablets, which used Co-XG-GA (F1–F5) as matrices, controlled drug release with zero-order release kinetics and could be used for controlled release dosage forms. Conclusion: Collectively, our results indicate that the Co-XG-GA can be applied as matrices in controlled release floating tablets